A book review on The implementation game what happens after a bill becomes a law by Eugene Bardach - Espiritu, Fe C. (1992)
The book is an analytical exploration of the problems encountered in the implementation of programs and why such problems occur, through an intensive review of specific programs in the United states in the 60's and 70's. The author also attempted to propose measures thru which such problems can be reduced, if not eliminated.
Typescript.
"March 1992."
Keywords: Policy sciences; Mental health laws -- California; United States -- Politics and government -- 1974-.